Method of calculation of tanks forced ventilation from the remnants of liquid products - Пузік, С. О.; Островський, Б. О.; Комар, Д. А. (Proceedings of National Aviation University (archive), 2013)
The advantages of gasoline compared to other petroleum products in terms of feasibility of their research. Calculations of the duration of ventilation and changes in the concentration of vapors of gasoline remains in the gas space of the vertical tank with a capacity of 1000 m3 (RUS-1000). Nomogram constructed for the quantitative forecast available liquid balances petrol A-95 and the time duration ventylyaiyi RUS-1000 from the remnants of the petrol